The Effectiveness of Handling Grand Theft by the Criminal Investigation Unit of Karanganyar Police to Create Justice in Law Enforcement - Alvian, Martin (Advances in Police Science Research Journal, 2024)
Grand theft is a crime with the highest crime index at the Karanganyar Police Station in 2020-2022. In the process of handling it, it also has a higher arrears case than other cases every year. This research aims to find out why the handling of grand theft by the Karanganyar Police Criminal Investigation Unit in order to create justice law enforcement has not been effectively implemented. The focus of the research is to answer questions related to organizational resources and the benefits of handling grand theft by the Karanganyar Police Criminal Investigation Unit. The concepts and theories used are the concept of effectiveness, the concept of handling, the concept of grand theft, the concept of Criminal Investigation Unit, the concept of the Karanganyar Police Station, the concept of creating, and the concept of justice law enforcement. While the theory used is organizational management theory, law enforcement theory and benefit theory. The research method used is field research and case studies, a qualitative approach, and descriptive analysis research. Sources of data obtained from primary and secondary data by using interviews, observation, and literature study methods. The research location is at the Karanganyar Police Criminal Investigation Unit. The results of the study show that 1) The implementation of handling grand theft by the Karanganyar Police Criminal Investigation Unit is generally good but not yet effective enough because there are still obstacles in the organizational resources such as humans, budget, infrastructure, systems and methods; 2) Grand theft handling has not provided maximum benefits to the people of Karanganyar Regency. This research concludes that the handling of grand theft can be effectively carried out if the organizational resources of the Karanganyar Police Criminal Investigation Unit can be managed in accordance with applicable standard rules and the SOTK rules. Also, Grand theft handling can be effective if the law enforcement process carried out by the Karanganyar Police Criminal Investigation Unit brings benefits to the community in the form of a feeling of joy/happiness, a sense of justice, and conducive environment conditions. If the problem of organizational resources and benefits is resolved, then justice law enforcement will be realized.